The role of culture in strengthening social capital in the GAPOKTAN (Farmers Group Association) Agro Prima at Padangsidimpuan, Indonesia (Research, Society and Development, 2020)
The objective of this research article was to discuss the benefit and the maintenance of social culture in the Gapoktan (Farmers Group Association), Agro Prima. The data were gathered by conducting in-depth interviews with 16 informants that consisted of the managers and the members of Agro Prima and the local government officials. The purpose was to find out the norms, the values, and the network of this group of farmers. The result showed that cultural values found in this group had brought about the strengthening of the element of social capital of its members. Their homogeneity of their religion and their ethnicity had caused them to be able to cope with any problems which arose in the Gapoktan, especially by using the principle of “holong mangalap holong” (being mutually affectionate). Besides that, the local people in this area firmly follow the cultural principle of “Tappal marsipagodangan, udut marsipaginjangan, marsipatua-tuaan aso dapot hadamean” (always instilling the sense of togetherness and the form of address for someone according to tradition followed from generation to generation) so that each member and the management of the group can maintain and develop harmonization in the organization. The use of this social capital can be seen from their activity in empowering in order to increase their welfare and economic condition. The Gapoktan, Agro Prima, also attempts to maintain and develop the organization so that it will become tenacious through the use of this social capital.